Naming and framing victims: Identity, ‘usable’ victimhood, and the spectral turn in transitional justice - Hearty, Micheál (International review of victimology, 2024)
Drawing from the literature on victimology, memory studies, and transitional justice, this article critically examines how representations of victimhood in post-conflict memory activism are rooted in contemporaneous claims-making. Using the collective remembrance of the events of August 1969 in Belfast as an empirical case study, it argues that memory activism centres on ‘usable’ victims whose victimhood can be seamlessly mapped onto preferred interpretations of the past in furtherance of post-conflict claims-making. Acknowledging the recent ‘spectral turn’ in transitional justice, the article explores how selective remembering and forgetting and the instrumentalization of selected identities through memory activism can transform otherwise problematic spectral figures into ‘usable’ victims. Once they have become ‘usable’, these victims become embedded in grassroots memory activism because they speak to claims-making over post-conflict truth and justice, the causes and consequences of past violence, and the post-conflict treatment of certain constituencies.